Association of sugar-sweetened beverage intake with maternal postpartum weight retention. Issue 13 (18th September 2021) - Mahabamunuge, Jasmin; Simione, Meg; Hong, Benjamin; Horan, Chrissy; Ayala, Sujata G; Davison, Kirsten; Redline, Susan; Taveras, Elsie M
Abstract: Objective: During the perinatal period, modifiable behaviours contributing to excess weight gain, including sugar-sweetened beverage (SSB) intake, are understudied. We examined the extent to which perinatal SSB intake affects postpartum weight retention (PPWR). Design: We measured SSB intake frequency in the third trimester and 1-month postpartum using the NHANES Dietary Screener Questionnaire. We assessed the association between SSB intake and PPWR (difference between 6-month postpartum and pregravid weight) using multivariable regression adjusted for socio-demographic and anthropometric variables. Setting: Greater Boston area. Participants: Three hundred forty-eight mother–infant pairs in the Rise and SHINE prospective birth cohort. Results: Mean age was 32·7 (sd 5·0) years; the sample was 47 % white, 32 % Hispanic, 14 % Asian and 7 % Black. Women reported mean daily SSB intake frequencies of 0·9 (sd 1·2) and 0·7 (sd 1·0) times/d in the third trimester and 1-month postpartum, respectively. At 6-month postpartum, average weight retention was 3·4 (sd 5·7) kg; 108 (sd 31 %) women had substantial PPWR, defined as a ≥ 5 kg increase between pregravid and 6-month postpartum weight. Each 1-time/d increment in SSB intake frequency during the third trimester ( β = 0·46 kg (95 % CI, 0·07, 0·86)) and 1-month postpartum ( β = 0·52 kg (95 % CI 0·03, 1·00)) was associated with higher weight retention at 6 months. Increased SSB intake frequency in the third trimester (OR: 1·37; 95 % CI 1·10, 1·75) and 1-month postpartum (OR: 1·17; 95 % CI 0·92, 1·52) resulted in higher odds of substantial PPWR. Conclusions: SSB consumption during the perinatal period is associated with higher weight retention at 6-month postpartum. Avoiding SSB may reduce the risk of excess weight retention.